Economic impacts of fall armyworm and its management strategies: evidence from southern Ethiopia. (10th January 2020) - Kassie, Menale; Wossen, Tesfamicheal; De Groote, Hugo; Tefera, Tadele; Sevgan, Subramanian; Balew, Solomon
Abstract: : This paper explores the economic implications of fall armyworm (FAW) and its management strategies by exploiting exogenous variation in FAW exposure amongst households in southern Ethiopia. We find that FAW exposure affects maize yield and sales negatively, but not consumption. Furthermore, we find evidence of crowding-in and intensification of insecticide use in response to FAW exposure. We also find suggestive evidence that existing extension service arrangements lack the capacity to deal with emerging threats such as FAW. Results imply that targeted interventions aimed at improving the effectiveness of control measures and institutional capacity would be key to reduce the adverse effects of FAW. Highlights: The economic impact of fall armyworm (FAW) in southern Ethiopia assessed Fall armyworm significantly reduces maize yields and maize sales A positive correlation observed between FAW exposure and intensity of insecticide use Existing individual FAW control strategies do not significantly abate losses from FAW Improving institutional capacity is essential to control FAW